2011
DOI: 10.1017/s037689291000086x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attitudinal and sociodemographic factors on pro-environmental behaviour in urban China

Abstract: SUMMARYChina currently faces severe environmental challenges, and information regarding the predictors of pro-environmental behaviour in China is needed to manage them. This study addresses this need by modelling the sociodemographic and attitudinal factors predicting pro-environmental behaviour in urban China. Pro-environmental behaviour was modelled as a function of environmental attitude (measured using the new environmental paradigm) and various sociodemographic characteristics. Respondents who were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
13
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 38 publications
10
111
13
12
Order By: Relevance
“…However, Korean and U.S. participants did not differ in pro-environmental behaviors that might be attributed to the new environmental paradigm that emerged among U.S. citizens in the late 1960s and early 1970s [50,51,53]. Environmentalism is a social issue about which U.S. citizens have strong opinions (a characteristic associated with low scores on long term orientation).…”
Section: Summary Of Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, Korean and U.S. participants did not differ in pro-environmental behaviors that might be attributed to the new environmental paradigm that emerged among U.S. citizens in the late 1960s and early 1970s [50,51,53]. Environmentalism is a social issue about which U.S. citizens have strong opinions (a characteristic associated with low scores on long term orientation).…”
Section: Summary Of Results and Discussionmentioning
confidence: 93%
“…This gender difference in environmental attitudes and behaviors was supported across 14 countries in Europe, Latin America and the U.S., and was consistently stronger for behaviors than for attitudes [52]. Chen et al [53] found that females practiced more pro-environmental behaviors than men. Women reported stronger environmental attitudes, concern, and behaviors than men (e.g., [54][55][56]).…”
Section: Pro-environmental Behaviors and Gendermentioning
confidence: 86%
“…Generally speaking, women demonstrate greater concern for the environment [34,[37][38][39][40][41][42]. For example, Hunter et al [43] concluded that compared to men, women are more committed to pro-environmental behaviors such as recycling, buying organic products and reducing automobile usage.…”
Section: Socio-demographic Factors Influencing Environmental Behaviormentioning
confidence: 99%
“…In line with previous literature, we control for several individual-and household-level characteristics that can influence energy efficiency adoptions, including age, education and building type among others (Chen et al, 2011;Hamilton et al, 2014;Mills & Schleich, 2012;Nair et al, 2010;Poortinga et al, 2003). A summary and description of the variables is presented in Table 2.…”
Section: Datamentioning
confidence: 99%